Characterization of Tribofilm with the Remaining Lubricating Oil by Raman Spectroscopy - Makoto Miyajima (Japanese Society of Tribologists, 2015)
As a first step to develop a method of in situ analysis of tribological behavior under oil lubrication, surfaces after the tribo-test with the remaining lubricating oil were analyzed with Raman spectroscopy. A ball-on-disk type tribo-test using a S45C disk and a SUJ2 ball was performed, and then its friction track of the disk surface was analyzed by Raman spectroscopy. Polysulfide and mineral oil were used as the lubricating oil without dilution. In addition to each lubricant peak, iron disulfide (FeS2) tribofilm peaks were detected on the friction track in the case of polysulfide, whereas the magnetite (Fe3O4) peak was detected on the friction track in the case of mineral oil. FeS2 intensity increased overtime in the case of the test at 200°C. In this way, tribofilm and oxide were detected as the remaining lubricating oil by Raman spectroscopy, which therefore suggests that Raman spectroscopy is an effective analysis method to investigate the formation process of tribofilm and oxide under oil lubrication.